نحو تعميم الزراعة الذكية مناخيا في سبيل تحقيق الأمن الغذائي: أدلة من تجارب بعض الدول الإفريقية: Towards Mainstreaming Climate-Smart Agriculture (CSA) in Order to Achieve Food Security: Evidence from Experiences of some African Countries - محمد بن موسى; عمر قمان; شهاب إليمي (Journal of North African Economies, 2025)
This study sought to highlight the features of the generalization of Climate-Smart Agriculture (CSA) in the continent of Africa in general and in each of (Ghana, Democratic Republic of the Congo, Mali, South Africa, Ethiopia) in particular. For this purpose, the concept of CSA was clarified, and the role of its tools in adapting climate change with farming systems was highlighted, in addition to diagnosing the reality of CSA in some African countries, as part of its endeavor to achieve their food security. Through a comprehensive literature review and a case study of some African countries, we found that despite all the efforts made, the lack of knowledge and skill of both households and extension officials prevented an accurate understanding of the adoption of CSA practices. Keywords: Climate-Smart Agriculture, Food Security, Climate Change, Africa .